Prevalence of cardiovascular risk factors amongst teaching staff of IIMSR medical college, Badnapur, Jalna, Maharashtra - Muneshwar, Sujata N.; Shafee, Mohd.; Giri, Purushottam A.; Gangwal, Pankaj R.; Doctor, Sadaf (International Journal Of Community Medicine And Public Health, 2017)
Background: Cardiovascular diseases are the number one cause of death globally. The cause of heart attacks and strokes are due to combination of risk factors- tobacco use, unhealthy diet, obesity, physical inactivity, alcohol use, hypertension, diabetes and hyperlipidaemia. Most cardiovascular diseases can be prevented by addressing these behavioural risk factors. The objectives were to study the prevalence of cardiovascular risk factors among teaching staff and to know the association of age and gender with cardiovascular risk factors. Methods: A cross-sectional study was carried out amongst teaching staff of IIMSR Medical College, Badnapur, Jalna, Maharashtra during the period of August to October 2016. All teaching staff of IIMSR Medical College was included in this study by purposive sampling method. Total number of staff who was more than 30 years of age was 80. The study was performed on 71 teaching staff as 9 denied participating (71 out of 80). Clinical parameters including weight, height, blood pressure and waist circumference was recorded. Blood sample was also collected. Statistical analysis was done by using appropriate statistical test like mean, percentage, standard deviation, student’s t test and chi square test. Results: Majority participants were male 50 (70.42%). The mean age of male was 42.6±13.4 yrs and female was 37.05±9.64 yrs. The mean weight (76.2±12.9), mean waist circumference (92.0±12.1) and mean BMI (27.02±4.44) were above the normal range amongst male participants. The mean height, mean weight, mean waist circumference, mean SBP, mean DBP, mean RBS, mean creatinine and mean BMI values were higher in males as compared to females. The difference was statistically significant. Hypertension was more common in older age with raised diastolic blood pressure which signifies that age is one of the most important risk factor. Conclusions: This study showed a high prevalence of cardiovascular risk factors and signifies the importance of health awareness among the staff members regarding the various cardiovascular risk factors.